Predictive modelling of whole-body vibration transmission through strategic locations of human body using artificial neural networks - Ali Murtoja Shaikh; Bibhuti Bhusan Mandal (International Journal of Occupational Safety and Health)
Introduction: Modelling the seated human body's response to whole-body vibration poses a formidable challenge due to its intricate reliance on factors encompassing anthropometry, postures, and vibration characteristics. While lumped parameter models are prevalent in this domain, their fixed weight necessitates modifications. Hence, a novel biodynamic model utilizing artificial neural network methodology was devised to simulate transmitted vibrations across strategic locations of body segments in seated individuals, facilitated by field vibration data.